Influence of Artificial Intelligence Chabot on Students’ Learning Experience in Public Secondary Schools in Abakaliki Education Zone, Ebonyi State - Igwe, M. U. (Journal of Research in Adult and Continuing Education, 2025)
This study investigated the influence of Artificial Intelligence (AI) Chabot on students’ learning experience in public secondary schools in Abakaliki Education Zone, Ebonyi State. The study sought to determine the influence of AI Chabot on grading and assessment process of students; personalized learning of students; and teacher-students’ collaboration learning process in public secondary schools. Descriptive survey research design was adopted for the study and data were collected using questionnaire “Influence of AI Chabot on students’ learning experience in public secondary schools Questionnaire (IAICSLE)” structured by the researcher. The population of the study was 88 English Language teachers and the sample was 45 teachers selected using purposive sampling technique. The use of purposive sampling technique enabled the researcher to select schools that have ICT units, constant power supply and digital tools. The reliability of the instrument was determined using Cronbach alpha approach. The analysis yielded the coefficient index of 0.84. Research questions were answered using the arithmetic mean while the standard deviation was used to determine the proximity of the respondents’ responses. The hypotheses were tested using t-test at 0.05 level of significance. The findings of the study revealed that AI Charbot has significant influence on grading and assessment process of students in public secondary schools; Artificial Intelligence Chabot has significant influence on personalized learning of students in public secondary schools; and that AI Chabot also has significant influence on teacher-students’ collaboration learning process of students. It was recommended that government should equip the schools with AI facilities and ensure constant power supply in order to improve on teaching and learning; the school authorities should constantly organize professional development programme such as seminar, workshop, symposium and conferences to update the teachers on the use of AI in teaching and learning; while the teachers should continuously make use of AI Chabot in teaching and learning so as to enhance grading and assessment process of students.
Keywords: Influence; Artificial Intelligence Chabot; Students’ learning experience; Ebonyi State